(NfORMACII DEWONA (B/s - (N{UVANOW(B, (NwASILIJ mUHSINOWI^s; (NaBDULIN(B, (Na(B.(Na(B.s; (NiNSTITUT GEOLOGI^ESKIH NAUK IM(B. (Nk(B.(Ni(B. (NsATPAEWA an kAZssrs ((NaLMA(B-(NaTA (B:s (NnAUKA(B. (NkAZssr(B,s, 1984)
(NbIBLIOGR(B.: (NS(B. 217-222s
Keywords: (NbIOSTRATIGRAFIQs; (NpALEOZOJSKIE OTLOVENIQs; (NpRIBALHA[XEs